2014
DOI: 10.3319/tao.2013.12.31.01(oc)
|View full text |Cite
|
Sign up to set email alerts
|

A Temporal Multiscale Analysis of the Waters off the East Coast of South Korea over the Past Four Decades

Abstract: We address the trends in water temperature variability to understand the local global warming effects through different time scales using daily sea surface temperature (SST) measurements from 1966 -2004. The abrupt SST changes off of the east coast of Korea are related to similar changes observed in the North Pacific. Seasonal water temperatures have increased by at least a factor of two or more in winter than in summer. While SSTs on annual timescales have increased significantly, SSTs on interannual timescal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…In fact, the SST in the East Sea rapidly increased over several decades [7,8,40]. Recently, Jo et al [40] reported that the rate of the SST increase was 0.041˝C¨y´1 in the east coast of Korea, which was much faster than the global average (0.005˝C¨y´1). However, no substantial increased SST was observed in this study during our investigation period (2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012), most likely because the observation period was not long enough to detect any small changes in the SST [13].…”
Section: Long-term Pattern Of the Annual Primary Production In The Eamentioning
confidence: 98%
See 1 more Smart Citation
“…In fact, the SST in the East Sea rapidly increased over several decades [7,8,40]. Recently, Jo et al [40] reported that the rate of the SST increase was 0.041˝C¨y´1 in the east coast of Korea, which was much faster than the global average (0.005˝C¨y´1). However, no substantial increased SST was observed in this study during our investigation period (2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012), most likely because the observation period was not long enough to detect any small changes in the SST [13].…”
Section: Long-term Pattern Of the Annual Primary Production In The Eamentioning
confidence: 98%
“…An increased SST may have caused the increased stratification of the surface mixed layer and, consequently, reduced the entrainment of major nutrients into the upper euphotic layer [38,39]. In fact, the SST in the East Sea rapidly increased over several decades [7,8,40]. Recently, Jo et al [40] reported that the rate of the SST increase was 0.041˝C¨y´1 in the east coast of Korea, which was much faster than the global average (0.005˝C¨y´1).…”
Section: Long-term Pattern Of the Annual Primary Production In The Eamentioning
confidence: 99%
“…The method is based on the simple assumption that all data comprise different simple intrinsic oscillatory modes that have individual physical meanings (Lee 2013). EEMD is an improved version of EMD that resolves a problem with EMD: mode mixing (Wu & Huang 2004;Jo et al 2014). The EEMD method decomposes a time series into a finite number of IMFs) and a residual monotonic function through a sifting process (Huang et al 1998;Wu & Huang 2004;Franzke 2012).…”
Section: Eemdmentioning
confidence: 99%
“…The nutrient input into surface layer would be declined by a strong stratification, which makes a weak vertical mixing under ongoing climate change [28]. Recently, Jo et al [7] reported that the increasing SST in the east coast of Korea is much faster than the global average. Indeed, decreasing field-measured nitrate concentration was observed in the southwestern EJS (i.e., Ulleung Basin) over the recent decade from 2003 to 2012 [6], though we did not observe the decreasing trend in SSN concentration in the entire EJS.…”
Section: The Spatial and Temporal Variation Of Sea Suface Nitrate (Ssmentioning
confidence: 99%
“…Various changes in physical, chemical and biological properties have been reported in the East/Japan Sea (EJS) during last several decades [1][2][3][4][5][6][7][8]. Particularly, a dramatic change in the vertical distribution of the chemical properties and sea surface temperature of the winter and spring was observed in the southern EJS during the last few decades [2][3][4].…”
Section: Introductionmentioning
confidence: 99%